2019
DOI: 10.1155/2019/6456032
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aberrant IGF-I Signaling in Diabetic Male Rat Retina Prevents and Reverses Changes of Diabetic Retinopathy

Abstract: Hyperglycemia results in inhibition of cleavage of integrin-associated protein (IAP) thereby allowing it to bind to SHPS-1 which results in pathophysiologic changes in endothelial function. This study determined if an anti-rat IAP antibody directed against the SHPS-1 binding site which disrupts IAP/SHPS-1 association could inhibit these pathophysiologic changes. The anti-IAP antibody inhibited IGF-I-stimulated SHPS-1, p52Shc, MAP kinase phosphorylation, and proliferation in endothelial cells. To determine if i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
2
1
Order By: Relevance
“…It is also in line with previous clinical findings that demonstrated that high systemic IGF-1 levels are correlated with higher prevalence and severity of DR [ 13 , 14 ]. The findings of the present study are further supported by the missing process of pathological neovascularization observed in knockout models using IGF-1 receptor suppression [ 26 , 27 ]. Similarly, patients with genetically low IGF-1 levels show fewer vascular branching points in the retinal vasculature, underlining the critical role of IGF-1 in the development of vascularization [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…It is also in line with previous clinical findings that demonstrated that high systemic IGF-1 levels are correlated with higher prevalence and severity of DR [ 13 , 14 ]. The findings of the present study are further supported by the missing process of pathological neovascularization observed in knockout models using IGF-1 receptor suppression [ 26 , 27 ]. Similarly, patients with genetically low IGF-1 levels show fewer vascular branching points in the retinal vasculature, underlining the critical role of IGF-1 in the development of vascularization [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…The reason for these differences remain unclear; however, it is noticeable that, in this study, the blood sugar level of rats has ranged between 14-28 mmol/L, whereas, in our study, the blood sugar levels were consistently close to or above 30 mmol/L. Therefore, a difference in the level of hyperglycemia may have resulted in the differences observed in RLT [37].…”
Section: Discussioncontrasting
confidence: 66%
“…In certain tissues, IGF-1 seems to function more as a paracrine factor rather than an endocrine factor. Moreover, inhibiting abnormal IGF-1 signaling in the retina has been demonstrated to prevent and reverse diabetic retinopathy in male rats [63]. This reversal may be attributed to the synergistic collaboration of IGF-1 with dopamine in mitigating diabetic retinopathy by downregulating VEGF [64].…”
Section: The Relationship Between Igf-1 and Age-related Macular Degen...mentioning
confidence: 98%